Tropical Pancreatitis presented as early onset Diabetes Mellitus - Shrestha, R; Rajbhandari, Ashish; Shrestha, S; Bhattachan, CL (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Tropical pancreatitis (TP) is a special form of chronic pancreatitis seen in tropical countries and has been less commonly reported from Nepal. We present a young non alcoholic female with early onset Diabetes Mellitus whose further investigations revealed pancreatic duct stones and was diagnosed as a case of tropical pancreatitis and underwent modified puestow’s procedure.